2018
DOI: 10.3171/2016.10.jns161179
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial cavernous malformations adjacent to the corticospinal tract: surgical outcomes and predictive value of diffusion tensor imaging findings

Abstract: OBJECTIVE Diffusion tensor imaging (DTI) findings may facilitate clinical decision making in patients with supratentorial cavernous malformations adjacent to the corticospinal tract (CST-CMs). The objective of this study was to determine the predictive value of preoperative DTI findings for surgical outcomes in patients with CST-CMs. METHODS A prospectively maintained database of patients with CM referred to the authors' hospital between September 2012 and October 2015 was reviewed to identify all consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…By qualitatively and quantitively evaluating the DTI/DTT results, Lin et al found that CST score and lesion-to-CST distance were correlated with short-term postoperative neurological function, whereas others did not find such a correlation of DTI/DTT changes to mRS score at follow-up. [10][11][12]19,21 In comparison, we found that the CST score was an independent predictor of postoperative muscle strength and mRS score at discharge. As CST scores reflect the severity of injury to the pyramidal tracts, a high score indicates that the tracts have already been damaged and are more vulnerable to surgical manipulation; in this case, patients are very likely to suffer from deteriorated or new neurological deficits, thus correlating with weaker muscle strength and worse postoperative mRS score.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…By qualitatively and quantitively evaluating the DTI/DTT results, Lin et al found that CST score and lesion-to-CST distance were correlated with short-term postoperative neurological function, whereas others did not find such a correlation of DTI/DTT changes to mRS score at follow-up. [10][11][12]19,21 In comparison, we found that the CST score was an independent predictor of postoperative muscle strength and mRS score at discharge. As CST scores reflect the severity of injury to the pyramidal tracts, a high score indicates that the tracts have already been damaged and are more vulnerable to surgical manipulation; in this case, patients are very likely to suffer from deteriorated or new neurological deficits, thus correlating with weaker muscle strength and worse postoperative mRS score.…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, it may have promising value for the prediction of postoperative neurological function. 12,15,19 However, as brainstem gliomas behave differently from cavernous malformations and their ability to infiltrate the normal brain may vary depending on their genetic characteristics, the role of DTI/DTT in brainstem glioma surgery merits investigation. In our study, the number of changes in the CSTs in the deviation, deformation, and interruption groups were very similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preoperative neuronavigation MRI with diffusion tensor imaging, and/or functional imaging obtained prior to surgery, may facilitate selection of safer surgical routes, and thereby reduce the likelihood of causing new postoperative deficits. 44,45…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…In addition to factors such as well-known hemorrhagic onset, unruptured BAVM, size, and deep venous drainage that are included in the Spetzler-Martin (S-M) grading scale [1][2][3][4], several surgical risk factors for eloquent BAVM have been reported in recent years, such as cortical reorganization and plasticity of motor area visualized via functional magnetic resonance imaging (fMRI) [5], BAVM lesion-tocorticospinal tract (CST) distance assessed by diffusion tensor imaging (DTI) [6,7], and BAVM lesion-to-activation area distance (LAD) assessed by fMRI [8]. They can help predict postoperative neurological outcomes in the eloquent area and these factors contributed to acceptable long-term outcomes [6,9], along with transient but finally reversible surgical morbidity.…”
Section: Introductionmentioning
confidence: 99%